The inter-annual variability in the onset of the enhanced chlorophyll-a east of Madagascar - Oozeeraully, Yuneeda Bibi Naheed (Marine Research (MA-RE) Institute, 2015)
Chlorophyll-a concentration is a measure of phytoplankton biomass and is therefore used as a proxy for primary production. The chlorophyll bloom occurring in the South western Indian Ocean is one of the major blooms in the open ocean and is subject to controversies about its formation, propagation and termination mechanisms. In this study, the region was divided into two sub-regions, the South East region (48°E-66°E, 24°S-30°S) and the East region (70°E-88°E, 24°S-30°S) and satellite datasets of chlorophyll-a, sea surface temperature, wind speed and direction and sea surface height were analysed. A bloom was characterized by twice the mean level of the sub-region (~0.08mg/m3) and three bloom years were identified: 2004, 2006 and 2008. The timing, propagation and termination of the bloom showed spatial and temporal variability. The wavelet analysis revealed a semi-annual signal for 2006 and 2008 and an annual one in 2004 due to the gradual decline in the concentration of chlorophyll-a. The transport of the bloom is affected by the passage of eddies where the concentration of chlorophyll-a is higher in the core and around the edges in cyclonic and anticyclonic eddies respectively. The bloom could be present at the sub-surface level throughout the years but is only apparent at the surface during specific years.